At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine which rearranged and simplified equation cannot be solved using the quadratic formula, let’s analyze each equation step by step.
### Equation A: [tex]\(5x^2 - 3x + 10 = 5x^2\)[/tex]
1. Subtract [tex]\(5x^2\)[/tex] from both sides:
[tex]\[ 5x^2 - 3x + 10 - 5x^2 = 0 \][/tex]
2. Simplify:
[tex]\[ -3x + 10 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ -3x + 10 = 0 \][/tex]
This is a linear equation, not a quadratic equation.
### Equation B: [tex]\(5x^2 - 3x + 10 = 2x^2 + 21\)[/tex]
1. Subtract [tex]\(2x^2 + 21\)[/tex] from both sides:
[tex]\[ 5x^2 - 3x + 10 - 2x^2 - 21 = 0 \][/tex]
2. Simplify:
[tex]\[ 3x^2 - 3x - 11 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ 3x^2 - 3x - 11 = 0 \][/tex]
This is a quadratic equation.
### Equation C: [tex]\(2x - 4 = 2x^2\)[/tex]
1. Subtract [tex]\(2x^2\)[/tex] from both sides:
[tex]\[ 2x - 4 - 2x^2 = 0 \][/tex]
2. Simplify:
[tex]\[ -2x^2 + 2x - 4 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ -2x^2 + 2x - 4 = 0 \][/tex]
This is a quadratic equation.
### Equation D: [tex]\(x^2 - 6x - 7 = 2\)[/tex]
1. Subtract 2 from both sides:
[tex]\[ x^2 - 6x - 7 - 2 = 0 \][/tex]
2. Simplify:
[tex]\[ x^2 - 6x - 9 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ x^2 - 6x - 9 = 0 \][/tex]
This is a quadratic equation.
### Conclusion:
The only equation that simplifies to a linear equation (and not a quadratic equation) is:
[tex]\[ 5x^2 - 3x + 10 = 5x^2 \][/tex]
Thus, the equation that cannot be solved using the quadratic formula is:
Equation A: [tex]\(5x^2 - 3x + 10 = 5x^2\)[/tex]
### Equation A: [tex]\(5x^2 - 3x + 10 = 5x^2\)[/tex]
1. Subtract [tex]\(5x^2\)[/tex] from both sides:
[tex]\[ 5x^2 - 3x + 10 - 5x^2 = 0 \][/tex]
2. Simplify:
[tex]\[ -3x + 10 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ -3x + 10 = 0 \][/tex]
This is a linear equation, not a quadratic equation.
### Equation B: [tex]\(5x^2 - 3x + 10 = 2x^2 + 21\)[/tex]
1. Subtract [tex]\(2x^2 + 21\)[/tex] from both sides:
[tex]\[ 5x^2 - 3x + 10 - 2x^2 - 21 = 0 \][/tex]
2. Simplify:
[tex]\[ 3x^2 - 3x - 11 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ 3x^2 - 3x - 11 = 0 \][/tex]
This is a quadratic equation.
### Equation C: [tex]\(2x - 4 = 2x^2\)[/tex]
1. Subtract [tex]\(2x^2\)[/tex] from both sides:
[tex]\[ 2x - 4 - 2x^2 = 0 \][/tex]
2. Simplify:
[tex]\[ -2x^2 + 2x - 4 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ -2x^2 + 2x - 4 = 0 \][/tex]
This is a quadratic equation.
### Equation D: [tex]\(x^2 - 6x - 7 = 2\)[/tex]
1. Subtract 2 from both sides:
[tex]\[ x^2 - 6x - 7 - 2 = 0 \][/tex]
2. Simplify:
[tex]\[ x^2 - 6x - 9 = 0 \][/tex]
3. The simplified equation is:
[tex]\[ x^2 - 6x - 9 = 0 \][/tex]
This is a quadratic equation.
### Conclusion:
The only equation that simplifies to a linear equation (and not a quadratic equation) is:
[tex]\[ 5x^2 - 3x + 10 = 5x^2 \][/tex]
Thus, the equation that cannot be solved using the quadratic formula is:
Equation A: [tex]\(5x^2 - 3x + 10 = 5x^2\)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.